2011
DOI: 10.1002/ccd.22798
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous retrieval of the locked helex septal occluder

Abstract: The HELEX device is approved for percutaneous closure of an atrial septal defect (ASD). It is also often used off-label to close patent foramen ovale (PFO). The device is well tolerated because it is very flexible, but this characteristic increases the likelihood of embolization of locked implants. While the company provides a mechanism to retrieve devices that do not lock correctly, retrieval of locked and released devices is much more difficult. A case of percutaneous retrieval of an embolized, locked HELEX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another patient required placement of an Amplatzer device due to postprocedure embolization of the originally placed 25‐mm Helex device. This case and the description of the method of retrieval have been previously reported .…”
Section: Resultsmentioning
confidence: 87%
“…Another patient required placement of an Amplatzer device due to postprocedure embolization of the originally placed 25‐mm Helex device. This case and the description of the method of retrieval have been previously reported .…”
Section: Resultsmentioning
confidence: 87%
“…All device groups except for the Amplatzer Cribriform group had patients who complained of episodic palpitations. Unique adverse events include prompt surgical extraction of the PFO closure device due to a wire frame fracture causing cardiac tamponade ( n = 1, Cardioform group) (submitted for publication), device embolization requiring endovascular removal and percutaneous placement of a new device ( n = 1, Helex group), and thrombus formation on the device ( n = 3, CardioSEAL group) …”
Section: Resultsmentioning
confidence: 99%
“…In ours and the previously reported cases [12,13], a GooseNeck snare was used to successfully retrieve the HELEX® device. The HELEX® device consists of a single nitinol wire with a mounted ePTFE occlusion membrane.…”
mentioning
confidence: 84%
“…Both cases happened within 24 h of implantation. Poommipanit et al [12] described successful percutaneous retrieval of the HELEX® device that embolized to the aorta without significant complications. Yared et al [13] reported retrieval of a HELEX® device that was caught within the tricuspid valve apparatus.…”
mentioning
confidence: 98%
See 1 more Smart Citation